1967
DOI: 10.1021/ac60250a036
|View full text |Cite
|
Sign up to set email alerts
|

Infrared analysis

Abstract: A new method for the infrared analysis of multicomponent gas mixtures which involves a condensed phase sampling technique employing commercially available cryogenic equipment is described. Only a few micromoles of material are required for positive qualitative identification of most chemical species; hence, the method is sensitive and suitable for impurity analysis. The technique is very general in its applicability. Structurally similar molecules are readily differentiated, and molecules differing only in iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A preliminary comparison of "pulsed" deposition (16,17) with the usual continuous deposition approach has led us to conclude that the former approach offers only a small saving in time while resulting in poorer isolation of PAH molecules in the matrix. These results, coupled with the greater complexity of apparatus required to perform pulsed deposition of analytes which are not gases at room temperature, appear to indicate that pulsed deposition will not be generally useful in the IR analyses of PAH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary comparison of "pulsed" deposition (16,17) with the usual continuous deposition approach has led us to conclude that the former approach offers only a small saving in time while resulting in poorer isolation of PAH molecules in the matrix. These results, coupled with the greater complexity of apparatus required to perform pulsed deposition of analytes which are not gases at room temperature, appear to indicate that pulsed deposition will not be generally useful in the IR analyses of PAH.…”
Section: Resultsmentioning
confidence: 99%
“…Since the initial description of the technique by Whittle, Dows, and Pimentel (1) in 1954, MI has been widely used, particularly for spectroscopic characterization of transient species; infrared (IR) absorption spectroscopy has often been employed in such studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, MI-IR spectroscopy has received very little consideration as a technique for the qualitative and quantitative (15) analysis of stable species, though Rochkind (16,17) has demonstrated that a variant of the conventional MI procedure can be successfully employed for the quantitative IR analysis of specific compounds in mixtures of gases.…”
mentioning
confidence: 99%
“…This mixture was deposited onto the cold window held at ϳ8 K using the pulsed deposition technique. [43][44][45][46] Typical conditions were as follows: 1 ms pulse duration, 10 Hz repetition rate, and 2 h deposition time.…”
Section: A Matrix Isolation Experimentsmentioning
confidence: 99%
“…Application of the matrix-isolation technique as a routine analytical method for the spectroscopic identification of unknown compounds has not been widely practiced. An early application of the matrix-isolation technique to the analysis of permanent gases was demonstrated by Rochkind (4); gases were collected in inert matrices by the rapid release of small quantities of premixed sample and argon onto a cold surface. The infrared bands of the trapped species in the resulting matrices were sufficiently sharp to allow the identification of several components deposited concurrently in a matrix.…”
mentioning
confidence: 99%